Removal of Dyes from Textile Wastewater Using Modified Eggshell Powder: Optimization and Application - Abdul Rahman, Nur Farisha Norhirman; Abdul Hamid, Nor Hazren (Progress in Engineering Application and Technology, 2026)
This study investigates the potential of chemically modified eggshell powder (ESP) as a low-cost bio-adsorbent for the removal of methylene orange (MO) dye. Eggshells were treated with hydrochloric acid to enhance their adsorption properties, and the modified ESP was characterized using Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM). The adsorption process was optimized via Response Surface Methodology (RSM) based on Central Composite Design (CCD), with contact time, adsorbent dosage, and initial dye concentration as key variables. The optimum conditions were identified as 75 minutes contact time, 1.5 g/L adsorbent dosage, and 90% initial MO concentration, achieving a maximum colour removal efficiency of 61.77% for synthetic dye solution. When applied to real textile wastewater, the process attained 39.14% colour removal, reducing the colour intensity from 327 ADMI to 199 ADMI, which complies with the Malaysian Standard B discharge limit. The findings demonstrate that modified ESP is a viable, eco-friendly, and cost-effective adsorbent for treating dye-laden textile effluent, contributing to sustainable wastewater management and waste valorisation.